Boccaccio fra la “misoginia” del Corbaccio e il “femminismo” del De mulieribus claris - Molnár, Annamária (Verbum – Analecta Neolatina, 2018)
Boccaccio’s concept of women has been raising a number of questions for centuries, to which the scientific research often gave extreme answers. Among these questions the most frequent one may be a stereotyped “misogynious Boccaccio” point of view, based on his Corbaccio, but leaving out of consideration his other works. But what reasons led to this opinion? How could a misread part of Decameron (VIII,7) support it? Is this kind of blame righteous on Boccaccio? To answer this problem the researcher should not only thoroughly investigate Corbaccio and provide an overview of the full Boccaccian oeuvre but also clarify certain questions of literary genres and traditions of Ancient and Medieval literature that have fallen into oblivion.